Method of Integral Assessment of Soil Quality in Rural-Urban Areas Based on the Fuzzy Logic - Ivashchuk, Olga A.; Fedorov, Vjacheslav I.; Koskin, Alexandr V.; Shcherbinina, Natalia V.; Zhuravlev, Maxim D. (International Journal of Engineering and Technology, 2018)
This article proposes a method of integral assessment of soil quality in rural-urban areas based on the fuzzy logic, both from the standpoint of the possibility of living in a given territory, and from the point of view of the possibility of keeping subsidiary farming. There are determined the linguistic variables describing the main soils components of rural-urban areas and terms describing the meaning of these variables. There are constructed the membership function that determine the ratio of the measured soil quality parameters to the terms and the rules of fuzzy inference. The authors developed an algorithm that describes this method.